PENGARUH APLIKASI TIKTOK TERHADAP PERKEMBANGAN MORAL ANAK USIA 5-6 TAHUN - Uhriyah, Sulfi; Eka Dheasari, Agustiarini (LPPM IAD Probolinggo, 2024)
The aim of this research is to determine the influence of the TikTok application on the moral development of children aged 5-6 years at AL - IKHLAS Kindergarten, Kademangan District. This research uses a qualitative method with a descriptive approach. Data was collected through observation analysis, interviews and documentation. The respondents in this study were three parents of students aged 5-6 years at TK AL – IKHLAS, Kademangan District. The research results show that the use of the social media platform TikTok has an important influence on children's moral development. Changes in behavior in early childhood caused by watching TikTok videos that involve deviations from the religious and moral values ​​taught at AL – IKHLAS Kindergarten, Kademangan District. Even though there are positive impacts such as increasing knowledge and increasing children's brain concentration, negative impacts also occur after watching videos on the TikTok application. Children easily imitate the style of adults on TikTok, use harsh language, and commit inappropriate actions as a result of watching TikTok content. This negative impact also spreads to learning activities at school. Therefore, it is important for parents to accompany their children when watching TikTok videos so that the videos their children watch can be directed towards watching positive videos. Keywords: Early Childhood, TikTok Application, Moral Development